Agouti-related protein as the glucose signaling sensor in the central melanocortin circuits in regulating fish food intake - Han, Juan; Liang, Xiaofang; Guo, Yanzhi; Wu, Xiaoliang; Li, Ziqi; Hong, Tiannuo (Frontiers in Endocrinology, 2022)
Agouti-related protein (AgRP) is a neuropeptide synthesized by AgRP/NPY neurons, transcribed as 132 amino acids in humans and 142 amino acids in fishes. AgRP neurons are activated by hormonal signals of energy deficit and inhibited by signals of energy surfeit, and has been demonstrated to have the ability to sense the dynamics of blood glucose concentration as the “glucose sensor” in mammals. It is widely recognized that AgRP is an endogenous antagonist of the melanocortin receptors MC3R and MC4R in the hypothalamus and exhibits potent orexigenic activity and control of energy homeostasis. Most fishes, especially carnivorous fishes can not make good use of carbohydrates, often causing feeding inhibition and metabolic diseases when fishmeal replaced by plant protein which limits utilization of plant protein in aquaculture industry. Our previous study showed that AgRP rather than NPY is the principal protein molecule that corresponded well to the feeding behavior in Japanese seabass (Lateolabrax maculatus) from the anorexia to adaptation stages in Ghrelin/Leptin-mTOR-S6K1-NPY/AgRP/POMC feed intake regulatory pathway responded to the plant-oriented protein which contains glucose. However, its regulatory function and mechanism are still not clear. This review attempts to offer an integrative overview about how glucose signals, converge on a molecular level in AgRP neurons of the arcuate nucleus of the hypothalamus to control fish food intake and energy homeostasis.